2017
DOI: 10.1016/j.exis.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the opportunities for mining companies to contribute to the United Nations Sustainable Development Goals in sub – Saharan Africa

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints -eprint.ncl.ac.uk Yakovleva N, Kotilainen J, Toivakka M. Reflections on the opportunities for mining companies to contribute to the United Nations Sustainable Development Goals in sub -Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 10 publications
0
30
0
1
Order By: Relevance
“…This "blinkeredness" (Gilberthorpe and Banks, 2012) can lead to corporate strategies that are incompatible with community structures, political paradigms, or other contingencies, creating problems that might otherwise have been avoided. These problems have led to calls for developing protocols that are regionally-or locally-specific (Salman et al, 2018;Yakovleva et al, 2017), yet our survey found only one framework that was tailored to a particular region. Despite this issue, nearly all of the frameworks drew from specific case study examples across the world.…”
Section: Developing Region-specific Protocolsmentioning
confidence: 97%
“…This "blinkeredness" (Gilberthorpe and Banks, 2012) can lead to corporate strategies that are incompatible with community structures, political paradigms, or other contingencies, creating problems that might otherwise have been avoided. These problems have led to calls for developing protocols that are regionally-or locally-specific (Salman et al, 2018;Yakovleva et al, 2017), yet our survey found only one framework that was tailored to a particular region. Despite this issue, nearly all of the frameworks drew from specific case study examples across the world.…”
Section: Developing Region-specific Protocolsmentioning
confidence: 97%
“…Developments in international legislation, along with increasing stakeholders' pressure, have urged companies to focus and manage multilateral and complex environmental, social and economic issues (Doz and Kosonen 2010). Although engagement with such subjects is not new, however, United Nations 2030 Agenda and SDGs have set the legal framework for private business to engage and demonstrate compliance and achievements towards measurable sustainability objectives (Yakovleva et al 2017). Under such regulatory and business evolution, CSR can constitute a strategic management tool that could assist companies to integrate and achieve their sustainability performance.…”
Section: Triple Bottom Line Approach To Sustainability and Csr Correlmentioning
confidence: 99%
“…In contrast, the international literature on mine closure has a greater focus on the social and economic impacts caused when a mine closes (Cochilo 2002;Yakovleva et al 2017). This is particularly true for mining in developing countries where mining operations employ significantly more people, at lower wages, and governments are less able to provide services to their citizens (Goh & Effendi 2017;Kotsadam & Tolonen 2016;Peck & Sinding 2009).…”
Section: Relinquishment In the Mining Industrymentioning
confidence: 99%